Study of charmonium production via the decay to $$p\bar{p}$$ p p ¯ at $$\sqrt{s} = 13\,TeV$$ s = 13 TeV - LHCb Collaboration (European Physical Journal C: Particles and Fields)
Abstract Charmonium production cross-section in proton–proton collisions is measured at the centre-of-mass energy $$\sqrt{s}=13\,\textrm{TeV}$$ s = 13 TeV using decays to $$p\bar{p}$$ p p ¯ final state. The study is performed using a data sample corresponding to an integrated luminosity of $$2.2\,\textrm{fb}^{-1}$$ 2.2 fb - 1 collected in 2018 with the $$\text{ LHCb }$$ LHCb detector. The production cross-section of the $$\eta _c$$ η c meson is measured in a rapidity range of $$2.0< y < 4.0$$ 2.0 < y < 4.0 and in a transverse momentum range of $$5.0< p_{\textrm{T}} < 20.0\,\textrm{GeV}\!/\!{ c}$$ 5.0 < p T < 20.0 GeV / c , which is extended compared with previous $$\text{ LHCb }$$ LHCb analyses. The differential cross-section is measured in bins of $$p_\mathrm{{T}}$$ p T and, for the first time, of y. Upper limits, at 90% and 95% confidence levels, on the $$\eta _c(2S)$$ η c ( 2 S ) and $$h_c(1P)$$ h c ( 1 P ) prompt production cross-sections are determined for the first time.